The absence of landscape. Reconstructing educational spaces in Cicero - Oliva, Matilde (Ciceroniana On Line, 2023)
Starting with the Partitiones oratoriae, the only Ciceronian work to present itself as a non-staged dialogue, this contribution investigates the spaces and settings of the various “didactic” moments in which Cicero is the protagonist. This with the objective to outline a new category of landscape, the didactic landscape, understood as the setting – real or imagined – of those occurrences in which Cicero presents himself explicitly as a teacher; instances that coincide with the space of the villa of Tusculum in a moment of otium. Anticipated in and prefigured by Crassus’ Tusculanum in the De oratore, Cicero’s villa in Tusculum is thereby studied as a real or parodic didactic setting in the Letters and as an evocative and personal one in the Tusculanae disputationes. The analysis suggests the hypothesis that this villa may constitute the environment of Cicero’s didacticism as also described in the beginning of the Partitiones oratoriae.